2017
DOI: 10.1200/po.16.00009
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Analysis and Functional Imaging Provide Complementary Approaches for Comprehensive Disease Monitoring in Metastatic Melanoma

Abstract: Purpose Circulating tumor DNA (ctDNA) allows noninvasive disease monitoring across a range of malignancies. In metastatic melanoma, the extent to which ctDNA reflects changes in metabolic disease burden assessed by 18F-labeled fluorodeoxyglucose positron emission tomography (FDG-PET) is unknown. We assessed the role of ctDNA analysis in combination with FDG-PET to monitor tumor burden and genomic heterogeneity throughout treatment. Patients and Methods We performed a comprehensive analysis of serial ctDNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
84
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 28 publications
17
84
2
2
Order By: Relevance
“…This study is, therefore, one of very few trials to prospectively assess treatment outcomes after administration of targeted therapy based exclusively on a ctDNA test result (Remon et al, 2017). Further investigation among larger groups of patients will be needed to demonstrate how frequently plasmabased assessments of targetable somatic mutations improve patient outcomes when such a mutation is not revealed via tumor-based molecular testing (Thierry et al, 2014;Wong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is, therefore, one of very few trials to prospectively assess treatment outcomes after administration of targeted therapy based exclusively on a ctDNA test result (Remon et al, 2017). Further investigation among larger groups of patients will be needed to demonstrate how frequently plasmabased assessments of targetable somatic mutations improve patient outcomes when such a mutation is not revealed via tumor-based molecular testing (Thierry et al, 2014;Wong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Intrapatient trends observed among serial ctDNA measurements were shown to differentiate progressive disease from an immune-related tumor response (Lee et al, 2018a, b). In addition, patients with advanced melanoma receiving inhibitors of the mitogen-activated protein kinase (MAPK) pathway showed marked increases in ctDNA that preceded the radiographic appearance of progressive disease, suggesting genomic changes linked to acquired drug resistance (Gray et al, 2015;Wong et al, 2017). Among patients with high-risk resected melanoma, ctDNA levels have been shown to predict disease relapse (Lee et al, 2018a,b).…”
Section: Introductionmentioning
confidence: 99%
“…47,48 For example, in patients with melanoma, ctDNA levels were correlated with metabolic disease volume, estimated with 18 F-labelled fluorodeoxyglucose positron emission tomography. 49,50 Therefore, the ctDNA level was a complex reflection of tumor biology, rather than simply associated with tumor burden or the number of dying cells. This finding suggested that ctDNA measurements might be more relevant to advanced stages of the disease and less relevant to precancerous lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Others also found a correlation between serial ctDNA analysis of BRAF and NRAS status and tumor response. PFS was longer in patients with an early decrease (1-4 weeks post-treatment) in ctDNA levels than in patients with unchanged or increased ctDNA levels post-treatment (HR = 2.6; p = 0.05) [98]. In the post-surgical setting, ctDNA analysis of BRAF and NRAS mutations predicted OS in 161 patients with high-risk stage II/III melanoma who underwent surgical resection followed by adjuvant bevacizumab for 1 year [99].…”
Section: Melanomamentioning
confidence: 92%